Curriculum of ethnic-racial relations at a faculty of dentistry - Melo, Fabricio de Medeiros; Riscado, Jorge Luís de Souza (Education Policy Analysis Archives, 2021)
The aim of this study was to verify the presence of ethnic-racial themes in the undergraduate course in dentistry, in order to identify approaches on ethnic-racial relations and health of the Black population in the pedagogical project and in the contents of the curricular matrix of the course. The methodology was based on a documentary study, exploratory and qualitative, supported by the recommendations of the Curricular Guidelines for Ethnic-Racial Relations, Black Population Comprehensive Health Policy and Curricular Guidelines for the Dentistry Course. The research was limited to the critical analysis of documents of an undergraduate course in dentistry in Alagoas. Data were collected between February and April 2018, using an instrumental matrix from the following categories: Explicit Ethnic-Racial Relations and Black Population Health in the Fundamentals and Justifications for the Training of the Dental Surgeon; The Afro-Brazilian ethno-racial dimension in the objectives; Skills and Skills; Ethnic-Racial Relations in Organization and Content. The data were analyzed from a content analysis perspective. There is a silencing of ethnic-racial relations in the pedagogical project in the fundamentals and justifications, in the objectives and competences for the formation and in the approaches of the contents. The institution has aspects in the organization of the course and curricular matrix that allow to integrate this theme transversally.